The post-use evaluation of the new cutting edge textbook : The students' attitudes : - Huỳnh, Trí Thức (Can Tho University, 2015)
This study mainly aimed at evaluating the English New Cutting Edge textbook for intermediate lavel of proficiency on the basic of the attitudes of students